2020
DOI: 10.21776/ub.ijabs.2020.28.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Voluntary Disclosure With Corporate Governance as Moderating Variables

Abstract: Purpose — The purpose of this research is to analyze and prove the influence of independent variables that are proxied by profitability, liquidity, firm size on voluntary disclosure, and moderated by corporate governance variables. Design/methodology/approach — The object of the research is the companies listed on the IDX from 2012 through 2016. This research uses a purposive sampling method involving 45 annual company reports and uses multiple regression and MRA (Moderated Regression Analysis) as a data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Signaling theory argues that profit-making firms disclose voluntary information to signify their good performance to gain an advantage for their values Widayawati et al, 2020). Empirically, prior studies have reported mixed findings for the effect of firm profitability on voluntary disclosure.…”
Section: Voluntary Disclosure and Readability Of The Annual Reportmentioning
confidence: 99%
“…Signaling theory argues that profit-making firms disclose voluntary information to signify their good performance to gain an advantage for their values Widayawati et al, 2020). Empirically, prior studies have reported mixed findings for the effect of firm profitability on voluntary disclosure.…”
Section: Voluntary Disclosure and Readability Of The Annual Reportmentioning
confidence: 99%